Effects of L-arginine oral supplements in pregnant spontaneously hypertensive rats - Moura,José Ricardo Sousa Ayres de (2006)
PURPOSE: To evaluate the effects of L-arginine oral supplementation in spontaneously hypertensive pregnant rats (SHR). METHODS: Thirty SHR and ten Wistar-EPM-1 virgin female rats were used in the study. Before randomization, females were caged with males of the same strain (3:1). Pregnancy was confirmed by sperm-positive vaginal smear (Day 0). Wistar-EPM-1 rats served as counterpart control (C-1). SHR rats were randomized in 4 groups (n=10): Group Control 2, non-treated rats; Group L-Arginine treated with L-arginine 2%; Group Alpha-methyldopa treated with Alpha-methyldopa 33mg/Kg; Group L-Arginine+Alpha-methyldopa treated with L-arginine 2%+Alpha-methyldopa 33mg/Kg. L-arginine 2% solution was offered ad libitum in drinking water and Alpha-methyldopa was administered by gavage twice a day during the length of pregnancy (20 days). Blood pressure was measured by tailcuff plethysmography on days 0 and 20. Body weight was measured on days 0, 10 and 20. Results were expressed as mean ± SD (Standard Deviation). One-Way ANOVA/Tukey (or Kruskal-Wallis/Dunn, as appropriate) was used for group comparisons. Statistical significance was accepted as p<0.05. RESULTS: There was no significant weight gain in isolated L-arginine treated SHR. Mean blood pressure decreased in L-arginine-treated SLR compared with untreated-SHR rats. CONCLUSION: L-arginine oral supplementation reduces blood pressure in spontaneously hypertensive rats during pregnancy.